The Sahel on the edge of the abyss? Why U.S. counterterrorism engagement has failed to achieve its goal? - Zhu, Yuan; Gao, Wanni (Frontiers in Political Science, 2024)
The United States has emerged as a prominent actor in the international fight against transnational terrorism in the Sahel region of Africa since 2002, exerting significant political influence on regional affairs. Under the leadership of the United States, a coalition of Sahel countries has collaboratively established security programs, notably including the Trans-Saharan Counterterrorism Partnership (TSCTP). However, the U.S. counterterrorism strategy in the Sahel region has not only proven ineffective in containing the deterioration of regional security, but also has exacerbated the vulnerability to coups in recipient countries. The observed deterioration can be attributed to various driving factors, such as deviations in the willingness and ability to involve and the security traffic jam. We contend that the U.S.-Sahel counterterrorism partnership is fundamentally misaligned and plagued by a securitization problem. Firstly, a significant impediment to international cooperation lies in the United States’ pursuit of consolidating its dominant role in Sahel security affairs, which usually overlooks the pragmatic principle of ‘African solutions to African problems’. In the counterterrorism process, there is a misalignment between U.S. national interests and those of Sahel states. Furthermore, the United States’ extensive reliance on military strategies indicates a significant securitization of non-violent civil affairs in certain Sahel states, inadvertently creating an opportunity for genuine terrorist organizations to recruit members. In addition, U.S. interference in the internal affairs of Sahel states heightens the risk of coups, thereby undermining the legitimacy of U.S. leadership in the region. Currently, with both the withdrawal of the United Nations Stabilization Mission in Mali (MINUSMA) and France withdrawing their security forces from the Sahel region, there has a significant weakening effect on regional security capabilities. Therefore, it is imperative for the international community to collaborate with African nations and adopt more proactive measures to safeguard regional security and maintain order.